POLÍTICAS HABITACIONAIS NACIONAIS: OS DESAFIOS AO DIREITO DE MORADIA NOS ARRANJOS INSTITUCIONAIS DO PROGRAMA MINHA CASA MINHA VIDA: NATIONAL HABITATIONAL POLICIES: THE CHALLENGES ON THE RIGHT TO HABITATION IN THE INSTITUTIONAL ARRANGEMENTS OF THE MINHA CASA MINHA VIDA PROGRAM (Revista Direito em Debate, 2021)
The theme of the present work is the confrontation of the challenges to the right to habitation, with focus on national habitational policies. In this sense, the objective is to analise the institutional arrangements made under the “Minha Casa Minha Vida” habitational program with focus on the increase of participation in the program and in the enabling of the proposed objectives. This exam will consider the program in the context of the legal-institutional structure of the urban policy at a national level. The metodology will follow the inductive method, Initially, the “Minha Casa Minha Vida” program will be established as a public policy, aswell as the inclusion of habitation among the fundamental rights following the emenda constitucional nº 26/2000. Following that, the legislative efforts to guarantee the right to habitation will be highlighted, with them focusing on the harmonization between individual and collective rights and the processes of economic development and enviromental preservation, emphasizing the role of the Estatuto das Cidades in the consolidation of this fundamental right. It will then be evaluated, as a result, how the dynamics of the habitational program in question deals with the phenomena of ilegal cities and social exclusion, and likewise with the demands of the social movements related to habitation, to enable a conclusion about the program’s level of success in regards to contributing to the strenghtening and the asserting of the right to habitation in the local context.